PRINCIPLES OF TOLERANCE SUNAN KALIJAGA AND HIS CONTRIBUTION ON ISLAMIZATION OF JAVA - Santosa, Santosa; Armansyah, Yudi (Kontekstualita, 2013)
Abstrak: Islamisasi yang dilakukan Sunan Kalijaga dalam menyebarkan Islam di pulau Jawa, memberikan pengaruh yang besar bagi perkembangan Islam pada periode selanjutnya. Dengan mengembangkan ajaran Islam melalui pendekatan budaya, menjadikan Islam mudah diterima oleh masyarakat. Proses islamisasi yang dilakukan Sunan Kalijaga dalam menyebarkan agama Islam dalam kondisi masyarakat pada masa itu masih kental dengan kepercayaan lama (Animisme, Dinamisme, Hindu dan Budha). Proses islamisasi yang dilakukan Sunan Kalijaga dalam menyebarkan agama Islam di pulau Jawa tidaklah mudah, karena kondisi masyarakat pada waktu itu masih kental dengan kepercayaan agama lama (Animime, Dinamisme, Hindu dan Budha). Akan tetapi dengan kepiawaian Sunan Kalijaga, sikap masayarakat terhadap dakwahnya sangat baik dan sedikit demi sedikit mau menerima ajaran agama Islam, karena ia dalam menyebarkan agama Islam benar-benar memahami keadaan rakyat pada saat itu. Sunan Kalijaga menyadari begitu kuatnya pengaruh Hindu-Budha pada saat itu, maka ia tidak melakukan dakwah secara frontal, melainkan toleran dengan budaya-budaya lokal. Menurutnya, masyarakat akan menjauh kalau diserang pendiriannya. Dengan pola mengikuti sambil mempengaruhi, dia mampu mendekati masyarakat secara bertahap. Prinsipnya, kalau ajaran Islam sudah dipahami, dengan sendirinya kebiasaan lama akan hilang. Ia memaduhkan unsur kebudayaan lama (Seni ukir, Suara, Gamelan, dan Wayang). Kata-kata Kunci: Sunan Kalijaga, Islamisasi, Jawa.Abstract: Islamization conducted Sunan Kalijaga in spreading Islam in Java, giving great influence to the development of Islam in the later period. By developing the teachings of Islam through a cultural approach, making Islam readily accepted by the public. Islamisation process conducted Sunan Kalijaga in spreading the religion of Islam is not easy, because the conditions of society at that time still dominated by old beliefs (animism, dynamism, Hinduism and Buddhism). Sunan Kalijaga realize how strong the influence of "genuine faith" is. By following the pattern while affecting, he was able to approach the public gradually. In principle, it has been understood that the teachings of Islam, itself the old habits will be lost. Islamisation process conducted Sunan Kalijaga in spreading Islam in Java is not easy, because the conditions of society at that time still dominated by the old religious beliefs (Animime, dynamism, Hinduism and Buddhism). However, with the expertise of Sunan Kalijaga, the attitude of society towards preaching is very good and little by little to accept the teachings of Islam, as he was in spreading Islam truly understand the circumstances of the people at that time. Sunan Kalijaga realize how strong the influence of Hindu-Buddhist at the time, he did not do propaganda frontally, but rather tolerant with local cultures. According to him, people will move away if attacked stance. By following the pattern while affecting, he was able to approach the public gradually. In principle, it has been understood that the teachings of Islam, itself the old habits will be lost. He memaduhkan elements of the old culture (art carved, Voice, Gamelan, and Puppet). Keywords: Sunan Kalijaga, Islamization, Java.